HARNESSING SOLAR ENERGIE TECHNOLOGIES: A response to the energy crisis - Muzanenhamo, Leonard; Chikosha, Felix; Sixpence, Samuel; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2025)
Globally, harnessing solar energy technology, managing costs, depletion and pollution has become a topical theme. The study examined factors that determine solar energy technology (SET) adoption readiness by sampling 1510 households in South Africa, Botswana, Malawi, Seychelles, Zambia and Zimbabwe. Targeted user identifiers and capabilities improved perceived economic value of solar energy technology were established. Several perceived economic values, barriers and drivers were established as factors determining readiness of a society to adopt solar energy technologies. A model to determine solar energy technology adoption readiness was developed. The study recommended the need for government energy policies that promotes affordability of solar energy technologies. Furthermore, the issue of perceived uncertainty, beliefs about consequences and consumer asymmetric require interventions by development agencies and solar energy companies. Furthermore, there is need for e-platforms and mobile platforms to provide critical information of servicing, installation, backups and the creation of information hubs and innovation hubs.